Evaluasi Instalasi Pengolahan Air Limbah Domestik di Kecamatan Soreang Kabupaten Bandung Provinsi Jawa Barat - Eka Wardhani; Riza Azrilla Sulaeman; Nurul Maryam; Tazkia Safitri Nugraha; Akbar Anugerah Perkasa; Shafa Maharani; Athaya Zahrani Irmansyah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Soreang District is the capital of Bandung Regency, with a population that continues to grow due to infrastructure development. This area falls within the Citarum River basin. The domestic sector is the largest contributor of pollutants to this river. This area already has a wastewater treatment plant, which was built in 1991. The aim of this research is to evaluate the capacity of the constructed WWTP in order to determine whether or not it is still able to cope with the wastewater produced. The methods used are field observation, measurement and comparison with current design criteria. Based on the research results, the existing plant can only serve 250 heads of families. It is necessary to increase the capacity of the plant to cater for the growing population. The current condition of the plant is sub-optimal due to plant maintenance issues. In addition, the sewerage network is damaged and there are no experts available to operate the plant. The research findings call for efforts to rehabilitate existing wastewater treatment plants and increase their capacity. Domestic wastewater treatment will reduce the pollution load of the Citarum River.